Surgical care by non-surgeons in low-income and middle-income countries: a systematic review. (27th April 2015) - Hoyler, Marguerite; Hagander, Lars; Gillies, Rowan; Riviello, Robert; Chu, Kathryn; Bergström, Staffan; Meara, John G
Abstract: Background: Anecdotal evidence suggests that task-shifting or the redistribution of responsibilities from fully-trained surgeons to clinicians with fewer qualifications could become a major component of surgical care delivery in many low-income and middle-income countries (LMICs). Our goal was to summarise the scope of surgical task-shifting in LMICs through a systematic review of the medical literature. Methods: We searched PubMed, EMBASE, CINAHL, LILACS, and African Index Medicus databases for papers and abstracts published between 1975, and November, 2014, that provided original data regarding non-surgeon providers, the type and volume of operations they perform, and the outcomes they achieve. The search was done in English, French, Spanish, and Portuguese, and included terms related to surgery, non-physician providers, and LMIC country names. Outcomes included the number of non-physicians and non-surgeons practicing surgery in LMICs, their qualifications, practice models and locations, and the types and volume of operations performed. Findings: We identified 65 articles and 14 abstracts that described non-surgeon and non-physician providers performing 46 types of surgical procedures, across eight surgical disciplines, in 41 LMICs. These procedures extended beyond those recommended by WHO, such as male circumcision and emergency obstetric surgery. Non-surgeons and non-physicians provided a large amount of surgical care in some locations, including 90% of obstretric surgeries, 38·5% of general surgery procedures, and 43% of non-obstetric laparotomies at three separate hospitals. Of the 38 papers that specified urban or rural locations, 35 described task-shifting in rural areas or district hospitals. A variety of formal training models for surgical task-shifting were noted, including collaborations between national governments, WHO, and private non-governmental organisations. Surgical providers often had no formal surgical training, and did not operate under the supervision of a fully trained provider. Interpretation: Our results suggest that non-surgeon physicians and non-physician clinicians provide surgical care many in low-resource settings. A limitation of our study is that our search was conducted in only four languages. Because many studies described the same country, countries or regions in overlapping time frames, it was not possible to determine the total number of task-shifting providers. In view of the shortage of fully-trained surgeons in many LMICs, it seems likely that task-shifting is far more widespread than is indicated by the medical literature. More research is needed to accurately determine the full extent and implications of surgical task-shifting in LMICs worldwide. Funding: None.